Effects of on-pump and off-pump surgery in the Arterial Revascularization Trial. - Taggart, D; Altman, D; Gray, A; Lees, B; Nugara, F; Yu, L; Flather, M (2014)
OBJECTIVES: The Arterial Revascularization Trial (ART) is a randomized comparison of bilateral internal mammary artery (BIMA) versus single internal mammary artery (SIMA) grafting in coronary artery bypass graft (CABG) surgery and is one of the largest randomized trials of surgery ever conducted. ART is also one of the largest studies of contemporary CABG with a high proportion of off-pump surgeries (41%). The objective of this post hoc analysis was to evaluate the surgical process and 1-year outcomes for surgery performed on-pump compared with off-pump. METHODS: ART randomized 3102 patients with multivessel coronary artery disease (CAD) to SIMA or BIMA grafts to determine if BIMA grafts have an additional survival advantage at 10 years. The 1-year interim analysis showed an overall very low mortality and major morbidity rate irrespective of whether the procedure was with an SIMA or BIMA. The surgical process and 1-year outcomes were analysed according to whether surgery was performed on-pump or off-pump. RESULTS: Baseline variables were not statistically significantly different between on- and off-pump surgery within each treatment group after taking account of the effects of clustering by individual surgeons. At both 30 days and 1 year, there was a low incidence of death (1.2%, 2.3%), stroke (1.1%, 1.7%), myocardial infarction (MI) (1.4%, 1.9%), repeat revascularization (0.5%, 1.5%) and wound reconstruction (1.2%). A similar average number of grafts were performed with on- and off-pump surgery (median = 3), but the duration of surgery was 20-30 min and ventilation time ∼2 h shorter with off-pump surgery. Blood loss and platelet transfusions were lower in the off-pump group, with no difference in the need for balloon pump or renal support. Sternal wound reconstruction was similar with off-pump surgery in the SIMA group (0.5 vs 0.6%) and lower with off-pump surgery in the BIMA group (1.4 vs 2.2%). Repeat revascularization was marginally higher in off-pump patients at 30 days (0.8 vs 0.3%) and at 1 year (1.7 vs 1.3%). CONCLUSIONS: The outcomes of contemporary CABG are excellent with low mortality, stroke, myocardial infarction and need for wound reconstruction and repeat revascularization whether performed on-pump or off-pump. CLINICAL TRIAL REGISTRATION: Controlled-trials.com (ISRCTN46552265).